Konsep Semantic Management Document System untuk Cross-Data Pemerintah Kota Manado - Christopel H. Simanjuntak; Fitria C. Lahinta; Sintya P. Junaedy; Leony A Wenno; Stieven N. Rumokoy; Fata Nidaul Khasanah (Jurnal Kajian Ilmiah, 2024)
In this era of highly developed technology and information, work and technology must coexist in achieving maximum results. With existing technology, work can collaborate with each other without knowing place and time so as to optimize the output of work. This also happens in government, which is a medium to serve the community. The government must serve all the needs of its people well and precisely and quickly in the process so that satisfaction from the community can rise. It's just that many in the government, especially the city of Manado, for example, agencies still use data independently so that other agencies or governments cannot access it. The use of technology is only as an application that is specialized for the agency even though the processed data can be used for other agencies related to the data. This causes the wrong use of information technology in terms of bridging between human work and humans themselves. If left unchecked, the actual work that can be collaborated does not occur even though there is already technology in the business process. Therefore, a system and modeling of data management that is appropriate in bridging the applications of each agency is needed so that applications can access the same data without overhauling all applications that have been running in each existing agency. In this research, a semantic-based system concept is developed for a data management system that can be accessed by different agencies and even other government institutions. The system concept will carry ontology modeling as the basis of the system so that data can be conceptualized according to the designation of the data. The purpose of this research is to create a passing system and cross data or documents using semantics for all standalone systems in government agencies so that data is no longer uploaded repeatedly in each existing system.